Meckel’s diverticulum and indications for resection - Razrim Rahim (Clinical Case Reports, 2020)
Abstract Meckel's diverticulum (MD) is a rare congenital abnormality. Not all MD require resection. MD is resected when it is symptomatic; when it causes perforation, bleeding, or intestinal obstruction; or when malignancy is confirmed or suspected.